AI TECHNOLOGY AS A TOOL FOR THE DEPICTION OF BIOMORPHIC ART: CANDI SEWU AS AN OBJECT OF INSPIRATION FOR ARTWORK - Afatara, Narsen; Kholis, Achmad Nur (JURNAL IMAJINASI, 2025)
Temple as an Indonesian cultural heritage must be preserved through revisualization in artworks. Biomorphic style is one of the references in beautifying the temple in artwork. The creation process can involve AI as a tool to support the aesthetics of the work. The creation of this research-based artwork is done through observation, interview, and literature study techniques. The process of making image references is supported by the involvement of AI, namely Adobe's Firefly. The limitation of AI features in providing style references according to the artist makes the images presented less than optimal. AI in the process of making artworks depicting the aesthetics of Sewu Temple with a biomorphic style is only used in the reference search process. The creation of artworks is still fully done by humans as the main actors.